2021
DOI: 10.1186/s12955-021-01769-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the EORTC QLQ-C30 in Uganda

Abstract: Background Self-reported measures play a crucial role in research, clinical practice and health assessment. Instruments used to assess self-reported health-related quality of life (HRQoL) need validation to ensure that they measure what they are intended to, detect true changes over time and differentiate between subjects. A generic instrument measuring HRQoL adapted for use among people living with cancer in Uganda is lacking; therefore, this study aimed to evaluate the psychometric properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The aim of this study was to appraise the psychometric properties of the Spanish version of the EORTC QLQ-C30 in a sample of patients with varying diagnoses. The results support the use of the EORTC scale to gauge quality of life in patients with cancer and confirm the stability of its construct in different types of tumor, which has also been corroborated by other studies [4,32,33] As previously mentioned, the factorial structure found in this study is organized around two factors: Quality of life and Physical health. The first factor includes all the items on the scale, reflecting a plausible unidimensional structure, in which all the items exhibit suitable factor loadings and proper goodness-of-fit indicators and could reflect physical well-being in cancer patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The aim of this study was to appraise the psychometric properties of the Spanish version of the EORTC QLQ-C30 in a sample of patients with varying diagnoses. The results support the use of the EORTC scale to gauge quality of life in patients with cancer and confirm the stability of its construct in different types of tumor, which has also been corroborated by other studies [4,32,33] As previously mentioned, the factorial structure found in this study is organized around two factors: Quality of life and Physical health. The first factor includes all the items on the scale, reflecting a plausible unidimensional structure, in which all the items exhibit suitable factor loadings and proper goodness-of-fit indicators and could reflect physical well-being in cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…The reliability estimates of the sum scores evaluated by means of McDonal's omega (ω) was excellent, with values of 0.94 for quality of life and 0.86 for the physical health dimension. Other studies have yielded similar results in which the values ranged from 0.74 to 0.95 [4,32,33].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…For purposes of this study, we translated the EORTC QLQ-C30 (version 3.0) into Luganda language and culturally adapted the instrument in accordance with the procedure developed by EORTC [16]. This was followed by an evaluation of the psychometric properties of the Luganda and English versions, the two most spoken languages in the country [17]. The results provided evidence for the validity and reliability of the Luganda and English versions of the EORTC QLQ-C30 for assessment of HRQoL in adult Ugandans with cancer.…”
Section: The Eortc Qlq -C30mentioning
confidence: 99%
“…However, the cognitive scale did not reach acceptable internal consistency and needs further evaluation. The present study is based on the same sample that was used in the psychometric evaluation [17] and will now in detail describe the HRQoL of adult patients with cancer in Uganda.…”
Section: The Eortc Qlq -C30mentioning
confidence: 99%